RHEOLOGY OF RENNET INDUCED CURD MADE FROM BUFFALO MILK - I. Hussain; A. Grandison; A. Bell (Journal of Animal and Plant Sciences, 2012)
Batches of pasteurized buffalo milk were stored at +2°C and -18°C for 4 days, the latter was also thawed and refrozen. Rennet induced curd was made from these milk samples using a gelation temperature of 39°C and at a pH of 6.50.Small amplitude oscillatory rheometry (SAOR) was used to study the rheological properties of the rennet induced curd made from the milk samples. All samples were examined within their linear viscoelastic limits. Both the storage modulus (G’) and loss modulus (G”) increased with time after the initial rennet addition while the loss tangent (tan δ) decreased to a constant value (about 0.44) for both the frozen and unfrozen milk samples. These results were consistent with an overall increase in the strength of the “weak” viscoelastic system with time. The dynamic moduli values were consistently higher in the samples of curd made from unfrozen (+2°C) and following the 1st freeze/thaw cycle than those made following the 2nd freeze/thaw cycle. When the frequency dependence (0.01-10 Hertz, strain 1%) was examined for three types of samples, both the dynamic moduli (G’, G”) and loss tangent (tan δ) of curd were found to be frequency dependent. All of the samples showed the characteristics of “weak” viscoelastic systems with the storage modulus predominating over the loss modulus over all of the frequency range (0.01-10 Hertz). If the milk is stored for a period at subzero temperatures, it is likely that the protein is damaged (denatured) during the freeze/thaw cycle, decreasing the interactions present in the protein matrix on curd formation and reducing the overall strength (dynamic moduli) of the curd while essentially maintaining the same type of gel system/interaction type. However it is not clear why this occurred after the second, but not the first, freeze/thaw cycle.
Keywords: buffalo milk; rennet induced curd; storage modulus. loss modulus; loss tangent; freezing